2005
DOI: 10.1002/fuce.200500089
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sulfonated Poly(Ether Ether Ketone)/Polytetrafluoroethylene Composite Membranes for Fuel Cell Applications

Abstract: The sulfonated poly(ether ether ketone) (SPEEK) / polytetrafluoroethylene (PTFE) composite membranes were produced to aid the swelling properties. The PTFE porous films were used as reinforcing material for the SPEEK/PTFE composite membranes. Scanning electron micrographs showed that SPEEK resin was distributed uniformly in the composite membrane and completely plugged the micropores; there is a continuous thin SPEEK film present on the PTFE surface. The dimensional stability and mechanical strength of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…Different strategies have been developed to solve this problem. First, reinforced materials, such as polytetrafluorethylene, 13,14 inorganic carbon fibers, 15 ceramic oxides, 16 or silanol moieties, 17 were introduced into the polymer matrix to improve its mechanical, thermal, and structural stability. The stabilization effect can be owed to the reinforcement by additives and intermolecular interactions between the polymer and other components.…”
Section: Introductionmentioning
confidence: 99%
“…Different strategies have been developed to solve this problem. First, reinforced materials, such as polytetrafluorethylene, 13,14 inorganic carbon fibers, 15 ceramic oxides, 16 or silanol moieties, 17 were introduced into the polymer matrix to improve its mechanical, thermal, and structural stability. The stabilization effect can be owed to the reinforcement by additives and intermolecular interactions between the polymer and other components.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear, though, how the ePTFE matrix influenced the membrane properties, as no comparison with bulk SPS film was made. In another study, SPEEK/PTFE membranes (pore size, 0.3-0.5 μm; porosity, 85%) prepared from SPEEK solutions in N-methyl pyrrolidone (NMP) (Xing et al 2005) and N,Ndimethylacetamide (DMAC) (Wei et al 2012) demonstrated lower σ and water uptake and higher oxygen permeability, as compared with recast SPEEK films. The PEMFC performance was below that of both recast SPEEK and Nafion.…”
Section: Isotropic Pore-filling Membranesmentioning
confidence: 99%
“…The reinforcement materials used have included PTFE porous films, woven PEEKs, and fiber-glasses. The composite membranes have demonstrated improved properties, such as mechanical strength and dimensional stability [105]. Despite the lower EW of these composites, due to the addition of insulating reinforcement materials, a low resistance can be achieved by using thin membranes [106].…”
Section: Reinforced Composite Membranesmentioning
confidence: 99%